2021
DOI: 10.1038/s41598-021-87878-5
|View full text |Cite|
|
Sign up to set email alerts
|

Disruption of insect immunity using analogs of the pleiotropic insect peptide hormone Neb-colloostatin: a nanotech approach for pest control II

Abstract: This work continues our studies on the pleiotropic activity of the insect peptide Neb-colloostatin in insects. In vivo immunological bioassays demonstrated that hemocytotoxic analogs of Neb-colloostatin injected into Tenebrio molitor significantly reduced the number of hemocytes in the hemolymph and impaired phagocytosis, nodulation and phenoloxidase activities in the insects. Among the analogs tested, [Ala1]-,[Val1]-, [Hyp4]- and [Ach4]-colloostatin were particularly potent in disrupting cellular immunity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In our work, we demonstrated that nanodiamonds coupled with Neb-colloostatin (SIVPLGLPVPIG-PIVVGPR), an insect hemocytotoxic and gonadoinhibitory peptide isolated from the ovaries of the gray flesh fly Neobellieria bullata, can penetrate the insect cuticle. In various in vivo bioassays, we showed that this conjugate introduced into the hemocoel of the insect through the cuticle retained specific hemocytotoxic activity and disturbed the cellular and humoral immune responses of all the developmental stages of the Tenebrio molitor beetle [200].…”
Section: Discussion: Peptide Biosensors-advantages and Applicationsmentioning
confidence: 97%
“…In our work, we demonstrated that nanodiamonds coupled with Neb-colloostatin (SIVPLGLPVPIG-PIVVGPR), an insect hemocytotoxic and gonadoinhibitory peptide isolated from the ovaries of the gray flesh fly Neobellieria bullata, can penetrate the insect cuticle. In various in vivo bioassays, we showed that this conjugate introduced into the hemocoel of the insect through the cuticle retained specific hemocytotoxic activity and disturbed the cellular and humoral immune responses of all the developmental stages of the Tenebrio molitor beetle [200].…”
Section: Discussion: Peptide Biosensors-advantages and Applicationsmentioning
confidence: 97%
“…The hemocytes of insects freely circulating in the open circulation system of insects show numerous structural and functional similarities to mammalian white blood cells 34 and are very sensitive to the action of various biotic and abiotic factors 34 . For this reason, they are a perfect model for the in vivo detection of cytotoxic effects induced by nanomaterials 27 29 . There are a lot of reports in the current state of the art that graphene nanomaterials, after entering the body with blood and/or passing through physiological barriers, reach various organs, where they accumulate to a different extent.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in this study, we examined in vivo effect of borophene nanoflakes on the viability and function of the insect's immunocompetent cells (hemocytes) and their ability to produce ROS in these cells. The tests of the biocompatibility of borophene nanoflakes were conducted on the insect Tenebrio molitor 26 , which is a convenient experimental model for comprehensive in vivo studies of the effects of nanoparticles on various physiological parameters crucial for animal life 27 29 . Furthermore, the insect hemocytes present numerous structural and functional similarities to mammalian white blood cells which makes it even more interesting to study.…”
Section: Introductionmentioning
confidence: 99%
“…536709) and showed shutdown of specific genes but without any effect on the toxicity indicator gene. Nowicki et al 73 used Neb-colloostatin for eco-friendly pest control. They found that this type of hormone can cause immune disturbance for the treated insects and could help in insect control, especially on Tenebriomolitor.…”
Section: Discussionmentioning
confidence: 99%